Evaluation of Zn[Mn]-Al LDHs as Matrices for Release of B, Zn and Mn in A Simulated Soil Solution - H. Hatami; A. Fotovat (مجله آب و خاک, 2023)
Introduction Boron (B) has a dual effect on living systems, so that the concentration range within which B is changed from a nutrient to a pollutant is rather narrow. Although B plays essential roles in all living organisms, its long-term excessive uptake has adverse effects on either human beings or plants and animals. Furthermore, part of the B that can be used as fertilizer is highly soluble and easily leached into the soil profile leadsing to some problems such as decrease of fertilizer efficiency. Therefore, to improve agricultural productivity through its gradual uptake by plants, the increase of B adsorption in the soil solution is necessary. Many adsorbents have been used for the adsorption of B from aqueous solutions; however, layered double hydroxides (LDHs) have been considered as one of the most effective adsorbents as well as slow releaser fertilizers of inorganic anions such as nitrate, phosphate, etc. The formula of LDHs are typically denoted as [M1-x 2+M x 3+ (OH)2]x+ (An-) x/n .m(H2O), where M2+ and M3+ are divalent and trivalent cations, respectively, the significance of x is the molar ratio of M3+/(M3++ M2+) and An- is the intercalated anion. Although LDH materials are commonly prepared by combining two divalent and trivalent metals, more metals can be introduced in the brucite layer to achieve a large variety of composition and higher adsorption capacity. Stability of LDHs in soil can be affected by numerous factors (e.g. low molecular weight organic acids (LMWOAs)) leading to release of structural cations in addition to interlayer anion. However, there are scarce investigations that have evaluated the potential of ternary LDHs (e.g. Zn–Mn–Al LDH) in desorption of B (as interlayer anion) and release of Zn and Mn (as structural anions) in a simulated soil solution. Therefore, the objectives of this study were, i) to compare the desorption of B capacity of binary LDH (Zn–Al LDH) and ternary LDH (Zn–Mn–Al LDH) in the simulated soil solution, and ii) to investigate the effect of three different electrolytes (potassium nitrate, oxalic acid, and citric acid) on the release of Zn and Mn from synthesized LDHs. Materials and methods A modified urea hydrolysis method was employed to synthesize Zn–Al and Mn-substituted Zn–Al LDHs with Zn(+Mn)/Al molar ratio of 2. Herein the contents of Mn with respect to Zn corresponded to 2% and 10% molar ratio. Accordingly, the synthesized materials denoted as Zn–Al, Zn–Mn1 and Zn–Mn2 for the samples without Mn, with 2 and 10 mol% Mn with respect to Zn content. For investigation of B desorption at a concentration of 10 mM, 15 mL from equilibrium solutions were substituted with 15 mL of 0.03 M KNO3 and shaken for 240 min. Substitution was repeated four times and A modified urea hydrolysis method was employed to synthesize Zn–Al and Mn-substituted Zn–Al LDHs with Zn (+Mn)/Al molar ratio of 2. Herein the contents of Mn with respect to Zn corresponded to 2% and 10% molar ratio. Accordingly, the synthesized materials denoted as Zn–Al, Zn–Mn1 and Zn–Mn2 for the samples without Mn, with 2 and 10 mol% Mn with respect to Zn content. For investiigatigatingon of B desorption at a concentration of 10 mM, 15 mL from equilibrium solutions were substituted with 15 mL of 0.03 M KNO3 and shaken for 240 min. Substitution was repeated four times and B concentrations in extracts were measured by Azomethine-H method. Furthermore, the supernatant Zn and Mn concentrations were determined by GF-AAS (PG 900). This process was repeated for 1.25 mM oxalic acid and 1.25 mM citric acid to study the effect of these compounds on B desorption as well as release of Zn and Mn. B concentrations in extracts were measured by Azomethine-H method. Furthermore, the supernatant Zn and Mn concentrations were determined by GF-AAS (PG 900). This process was repeated for 1.25 mM oxalic acid and 1.25 mM citric acid to study the effect of these compounds on B desorption as well as release of Zn and Mn. Results and Discussion The adsorption and desorption isotherm were carried out to describe the distribution of B between the liquid and adsorbent. The isotherm data of synthesized LDHs were matched with Freundlich model. The values of 1/n in this model were found between 0 and 1 for all LDHs indicating favorable sorption of B on these compounds. The highest adsorption was observed for ternary LDHs (particularly Zn–Mn2) due to their higher specific surface area and also due to the ion exchange mechanism in combination with surface adsorption. However, the results showed that the percentages of B desorption by potassium nitrate, oxalic acid and citric acid were lower for Zn–Mn1 (19.4, 29.1 and 38.2%, respectively) and Zn–Mn2 (18.6, 28.2 and 35.9 %, respectively) than Zn–Al (30.8, 41.2 and 46.2%, respectively). This observation suggests that the type of LDH, B adsorption mechanism and background electrolyte can affect the amount of B desorption. Furthermore, after 4 successive desorption cycles, the concentration of Zn and Mn increased in the supernatants (particularly in organic acid electrolytes) suggesting dissolution mechanism possibility happened for the studied LDHs. Among the background electrolytes, citric acid was the most effective compound in releasing Zn and Mn, followed by oxalic acid and potassium nitrate. A reason for this such observations could be that with respect to chemical structure, citric acid by three carboxyl groups can form more chelate rings compared to oxalic acid, which contain two carboxyl groups. Therefore, it seems that B containing Zn–Mn–Al LDH may have potential to be used as a slow release fertilizer in soils to supply three essential elements, including B, Zn and Mn simultaneously. However, further studies are required to support such a hypothesis.